Utility and Validity of the Youth Level of Service/Case Management Inventory (YLS/CMI) for Young Offenders in Western Australia - Dellar, Kristie Chanel (Curtin University, 2022)
This thesis examines the validity and utility of the Youth Level of Service/Case Management Inventory general risk assessment tool for youth offenders in Western Australia. The measure was found to be a valid and reliable predictor of general recidivism. A shortened measure improved predictive validity for both Indigenous and non-Indigenous youth. The findings contribute to building an empirical base for best practice in risk assessment and risk management with West Australian youth offenders.